Analisis Risiko Produksi Usahatani Padi Sawah di Provinsi Bali - Suharyanto, Suharyanto; Rinaldy, Jemmy; Arya, Nyoman Ngurah (Universitas Muhammadiyah Yogyakarta, 2015)
This study aimed to analyze the risk of paddy rice farming and the impact of the use of farm inputs to the risk of rice production in Bali Province. The research was conducted in three districts of rice production centers, Tabanan, Buleleng and Gianyar during two cropping seasons in 2012. The data collected through interviews with 122 randomly selected farmers. Risk production of low land rice was analyzed by the coefficient of variation, while the factors that affect the risk of rice production were analyzed with multiple linear regression analysis with multiplicative heteroskedastic method. The result showed that the risk production of rice onÂ wet season and the land does not belong to his own status is higher than dry season and his own status. Production factors that significantly affect the risk of rice production are land, organic fertilizers and pesticides.